2017
DOI: 10.13189/ujer.2017.051219
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Teacher Candidates' Beliefs about Standardized Testing

Abstract: The purpose of this study is to examine the beliefs of prospective teachers' about standardized testing in terms of some variables. This piece of research is in survey model. The study is carried out with 442 randomly selected prospective teachers registered in different departments at Dicle University in Turkey during the 2015-2016 academic year. Selected teacher candidates are grouped under 5 fields according to the branches they have registered (social sciences, language education, mathematics and sciences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…Through the descriptive statistical analysis, the calculation of the mean and std. Deviation confirmed "very high" and "high" responses out of 14 questions based on the mean Interval Score Interpretation proposed by Kinay and Ardıç (2017). It indicated that students positively perceive the use of thinking skills in English language classrooms.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Through the descriptive statistical analysis, the calculation of the mean and std. Deviation confirmed "very high" and "high" responses out of 14 questions based on the mean Interval Score Interpretation proposed by Kinay and Ardıç (2017). It indicated that students positively perceive the use of thinking skills in English language classrooms.…”
supporting
confidence: 61%
“…In order to interpret the students' viewpoint, the data were analyzed descriptively using mean and standard deviation. Therefore, this study used the interpretation of Kinay and Ardıç (2017) to interprete students' perceptions. Table 2 below illustrates the mean interval score interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bay et all (2014) in their study found a significant difference between classroom teachers' beliefs and branch teachers' beliefs toward traditional learning approach. Kinay and Ardıç (2017) also have found a significant difference in prospective teachers' beliefs towards standard test in terms of department variable. Finally, Can and Arabacıoğlu (2009) found a significant difference in prospective teachers' epistemological beliefs in terms of department variable.…”
Section: Discussionmentioning
confidence: 72%
“…Alemdağ (2015) found that the epistemological beliefs of the prospective teachers enrolled in physical education department differ significantly in terms of grade variable. As for the study of Kinay and Ardıç (2017), they haven't found any significant difference in prospective teachers' beliefs toward standard tests in terms of grade variable.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation